2020
DOI: 10.3390/ani10111939
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Stylosanthes scabra Accessions as Forage Source for Ruminants: Growth Performance, Nutritive Value and In Vitro Ruminal Fermentation

Abstract: Feed shortage is the main cause of poor production performance in livestock under smallholder farmer’s in South Africa. Therefore, this study evaluated the growth performance, nutritive value and in vitro ruminal fermentation of Stylosanthes scabra accessions in climatic condition of Pretoria, South Africa as potential forage sources in order to improve feed quality and subsequently livestock production. Stylosanthes scabra accessions were planted in 6 m2 plots following a complete randomized block design with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…The improved degradability of rice straw after MA or MA+M pretreatment is due to the destruction of the cell wall structure of rice straw and the improvement of enzymatic hydrolysis efficiency. These findings suggest that the rice straw pretreated by MA or MA + M could provide more nutrients that can be absorbed and utilized by ruminants (Hymes-Fecht and Casper, 2021 ) and also imply a positive impact on animal performance (Mpanza et al, 2020 ). A previous study has also shown that the L. plantrum additives can improve in vitro degradation of elephant grass (Shah et al, 2021 ), and the IVDMD and IVNDFD increased by 13.97 and 32.69%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The improved degradability of rice straw after MA or MA+M pretreatment is due to the destruction of the cell wall structure of rice straw and the improvement of enzymatic hydrolysis efficiency. These findings suggest that the rice straw pretreated by MA or MA + M could provide more nutrients that can be absorbed and utilized by ruminants (Hymes-Fecht and Casper, 2021 ) and also imply a positive impact on animal performance (Mpanza et al, 2020 ). A previous study has also shown that the L. plantrum additives can improve in vitro degradation of elephant grass (Shah et al, 2021 ), and the IVDMD and IVNDFD increased by 13.97 and 32.69%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted at the University of Pretoria in the Department of Animal and Wildlife Sciences located at 25˚44'30''S, 28˚15'30''. Details on climate condition of the study area are described on our previous study [34]. The substrates that were used for the experiment were Eragrostis grass hay (hereafter referred as grass hay), five (9281, 11,252, 11,255, 11,595 and 11,604) accessions of Stylosanthes scabra forages.…”
Section: Study Site and Chemical Composition Of The Substratesmentioning
confidence: 99%
“…The substrates that were used for the experiment were Eragrostis grass hay (hereafter referred as grass hay), five (9281, 11,252, 11,255, 11,595 and 11,604) accessions of Stylosanthes scabra forages. The numbers assign to each accessions are according to International Livestock Research Institute (ILRI), Ethiopia who donated the seeds that were evaluation for adaptation [34]. Forages of Stylosanthes scabra accessions that were used in this study were produced during the evaluation study conducted in Pretoria [34].…”
Section: Study Site and Chemical Composition Of The Substratesmentioning
confidence: 99%
See 2 more Smart Citations